Teoría, política y sociedad : reflexiones críticas desde América Latina (CLACSO, 2018)
The diversity of themes and problems presented by the texts that make up this book is certainly extraordinary. So is the diversity of perspectives with which they are approached. Thematic diversity and theoretical plurality are, then, two of its main characteristics. This will be weakness or strength according to the criteria used for its assessment. As far as the editors are concerned, having been able to bring together such a variety of objects and perspectives in one collective volume is undoubtedly a positive thing. And this because this book is proposed, in the first place, as a map of the thematic and problematic interests that today cross the Latin American social sciences concerned with the theoretical reflection of their various objects of study. We believe that through these pages a panoramic vision of a good part of the intense and varied activity that social scientists carry out in our region can be achieved. From the Foreword by Ezequiel Ipar and Sergio Tonkonoff